Future materials engineering and industry application : selected, peer reviewed papars from the 2011 International Conference on future materials engineering and industry application, ICFMEIA 2011, August 4-5, 2011 Bali Island, Indonesia - Tan, Barry (Advanced materials research, 2012)
These are the proceedings of the 2011 International Conference on Future Materials Engineering and Industrial Application, held on August 4-5th, 2011 in Bali, Indonesia. The objective of ICFMEIA 2011 was to provide a forum within which researchers, educators, engineers, and government officials involved in the general areas of Future Materials Engineering and Industrial Applications could disseminate their latest research results and exchange views on the possible future research directions of these fields. The result is an up-to-date guide to the subject. Review from Book News Inc.: These pro.